Luminous measurement of LED lights in cost effective way using cylindrical method - Haque, Fahimul; Azad, Akm M.M.Abdul Malek (© 2016 Elsevier Ltd, 2018)
This article was published in the Measurement: Journal of the International Measurement Confederation [© 2016 Elsevier Ltd] and the definite version is available at : http://doi.org/10.1016/j.measurement.2016.11.028 The Journal's website is at: https://www.sciencedirect.com/science/article/pii/S0263224116306728?via%3Dihub